Research and trends in the studies of Collective Intelligence from 2012 to 2015 - Francisca Grimon; Jaime Meza; Monica Vaca-Cardenas; Jose M. Monguet (European Alliance for Innovation (EAI), 2017)
The interaction between groups of people and machines supports the transfer of knowledge and strengthen Collective Intelligence (CI) making it robust. The CI with the support of technology progresses through platforms and computer systems including ontology, clusters, agents, Web intelligence among others. This research consists of a content analysis of recent studies 2012-2015 on CI. After an extensive search of publications on electronic databases, two hundred and fifteen papers were selected and exposed in a document's analysis following the approach of Zott. In this research we identified three categories to consider: Learning, technology and decision-making. The analysis revealed that CI is strongly related with technology, supporting the processes of training people and promoting collaborative learning as a new form of literacy.